Conjugation reactions in the preparations of quantum dot-based immunoluminescent probes for analysis of proteins by capillary electrophoresis - Lišková, M; Voráčová, I; Klepárník, K; Hezinová, V; Přikryl, J; Foret, F (Analytical and bioanalytical chemistry, 2011)
A number of biologically important molecules, such as DNA, proteins, and antibodies, are routinely conjugated with fluorescent tags for high-sensitivity analyses. Here, the application of quantum dots in the place of bright and size-tunable luminophores is studied. Several selected bioconjugation reactions via zero-length cross-linkers, long-chain linkers, and oriented methods for linking of quantum dots with proteins were tested. Anti-ovalbumin, anti-proliferating cell nuclear antigen, anti-hemagglutinin, and anti-CD3 membrane protein as model antibodies and annexin V were used as high-specificity selectors. The reaction yield and efficiency of the prepared immunoluminescent probes were tested by capillary zone electrophoresis with laser-induced fluorescence detection.
Keywords: Antibodies; elektroforéza kapilární; Proteins; molekulární sondy; luminiscenční měření; Luminescent Measurements; Quantum Dots; imunoanalýza; proteiny; protilátky; Immunoassay; kvantové tečky; Molecular Probes; Electrophoresis, Capillary